An assessment of alternative social banking systems using T-Spherical fuzzy TOP-DEMATEL approach - Özdemirci, Fahrettin; Yüksel, Serhat; Dinçer, Hasan; Eti, Serkan (Elsevier Inc., 2023)
Assessment of alternative banking systems is a difficult problem with multiple and conflicting criteria. This study proposes a multi-criteria decision-making (MCDM) model for evaluating alternative social banking systems (with no interest charges) using a T-Spherical fuzzy Decision-Making Trial and Evaluation Laboratory (DEMATEL) called TOP-DEMATEL. First, a comprehensive literature review determines the factors affecting the performance of alternative systems. An analysis is carried out with the help of the T-Spherical fuzzy TOP-DEMATEL approach to determine the importance weights of the factors under consideration. The alternative social banking systems with no interest charges are designed to minimize the negative effects of interest on the economy. The causality analysis shows that the effective risk analysis and employment of qualified personnel were the most effective criteria on all other factors. In addition, the improvement of the technological infrastructure is also affected by all other factors. Effective risk analysis is determined as the most important criterion for the performance of the alternative banking system. In this context, a comprehensive risk analysis is required for the success of the new alternative banking system.
Keywords: Alternative Banking Systems; Decision-Making Trial and Evaluation Laboratory (DEMATEL); Fuzzy Logic; Multi-Criteria Decision-Making; T-Spherical; TOP-DEMATEL